Enzyme activity during a mesocosm experiment in the Peruvian upwelling system: biochemistry and phytoplankton - Kristian Spilling; Jonna Piiparinen; Eric Pieter Achterberg; Javier Arístegui; Lennart Thomas Bach; Maria-Teresa Camarena-Gómez; Elisabeth von der Esch; Martin A Fischer; Markel Gómez-Letona; Nauzet Hernández-Hernández; Judith Meyer; Ruth A Schmitz; et al. (PANGAEA, 2023)
The data is from a mesocosm experiment set up outside Lima, Peru to study the influence of upwelling of oxygen minimum zone (OMZ) water. The mesocosm bags were 2 m in diameter and extended from the surface down to 19 m depth, where the last 2 m was a conical sediment trap. Eight mesocosm bags were used and they were moored at 12.0555°S; 77.2348°W just north of Isla San Lorenzo where the water depth is ~30 m. The experiment was started 25 February 2017 by closing the mesocosm bags and were run for 50 days. Two treatments were used (water with different OMZ signature), each with four replicates. Water (100 m3) from the OMZ was collected from two locations and depths. The first was collected from 12.028323°S; 77.223603°W from 30 m depth, and the second one from 12.044333°S; 77.377583°W from 70 m depth. The original aim was to collect severe and moderate OMZ signature water (differing in e.g. nitrate concentrations) from the first and second site, respectively. This assumption was based on long-term monitoring data, however, the chemical properties (e.g. nitrate concentration) was more similar in these water masses than anticipated, rather reflecting low and very low OMZ signatures from site 1 and 2 respectively. To have a baseline of measured variables, the mesocosms where closed and environmental and biological variables were determined over 10 days. After this period, the OMZ water was added to the mesocosms in two steps on day 11 and 12 after the enclosure of the mesocosms. As the mesocosms contain a specific volume (~54 m3), the process of adding the OMZ water started with first removing water from the mesocosms. The water removed (~20 m3) was pumped out from 11-12 m depth. A similar volume of OMZ water, from both collection sites, was then pumped into four replicate mesocosms each. The OMZ water was pumped into the mesocosms moving the input hose between 14-17 m depth. The water collected at 30 m depth was pumped into mesocosms M1, M4, M5 and M8 having a low OMZ signature and water from 70 m depth into mesocosms M2, M3, M6 and M7 having a very low OMZ signature. Due a halocline at 12 m depth (see below), the added OMZ water was not immediately mixed throughout the mesocosm bag. Sampling took place every second day over a period of 50 days, and all variables were taken with an integrated water sampler (HydroBios, IWS) pre-programed to fill from 0 – 10 m depth and all samples consisted of this integrated samples from the upper 10 m. The samples were stored dark in cool boxes and brought back to the laboratory and processed right away. Sampling took place in the morning, and the samples were usually back in the laboratory around noon. Measured variables included inorganic nutrients, dissolved organic nutrients, extracellular enzyme activity: leucine aminopeptidase (LAP) and alkaline phosphatase activity (APA), and the phytoplankton and bacterial community composition.
In: Spilling, K et al. (2023): Enzyme activity during a mesocosm experiment in the Peruvian upwelling system [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.958426